Between Library and Research Centre: Metadata and Criticism - Pinheiro, Alcinda (2014)
Abstract: In order to promote the transfer of information and the development of knowledge, university librarians should proactively work with the academic community in well-organized transdisciplinary teams—involving teachers, researchers, students, and experts in various subjects. The concept of this very innovative practice has been developed and tested by the Faculty of Humanities Library, Lisbon University, and the University of Lisbon Centre for English Studies, focusing on the role played by libraries in canon-formation. We will now proceed to build an interactive website to publish our theoretical perspectives along with bibliographic records (UNIMARC format), including metadata related to marks of use. Furthermore, Richard Garnett’s “The International Library of Famous Literature” (London 1899), bio/bibliographical essays on Garnett as a scholar and librarian, and critical essays on the anthology will be published there. A link to the English edition is the next follow-up. Finally, two volumes of the Portuguese anthology (ca. 1910), based on the English one will also be made available on the website.